Aplikácia dvojstupňovej DEA metódy pri hodnotení efektívnosti poisťovní a bánk - Grmanová, Eva (Vysoké učení technické v Brně, Fakulta podnikatelská, 2013)
Purpose of the article: The article describe two-stage DEA technique and possibilities of application for efficiency measuring of insurance companies and banks. The article describe critically describe differences between application Two-stage DEA techniques and “classical” DEA techniques in the evaluation of insurance companies, banks. Methodology/methods: In this paper was applied secondary research. The secondary research was based on analysis of papers and literature published about Two-stage DEA techniques. Scientific aim: The aim of this paper is critically describe differences between application and “classical” DEA techniques in the evaluation of insurance companies, banks and describe of possibilities of exploitation in the evaluation of insurance companies, banks and custom system design of evaluation of insurance companies, banks. Findings: Two-stage DEA technique compare not only the efficiency of overall process but also learn the efficiency of part processes- sub-processes. Using the Two-stage DEA techniques enables to examine the efficiency of each of the two evaluated sub-processes and the product of efficiency of the subjects in different sub-processes is the same as the efficiency of the overall process. The aim of this approach is to compare the “contribution” of efficiency of each of the two measured sub-processes with the efficiency of the overall process. Conclusions: By complementing steps sequence compact of use of different statistic methods it is thanks to two-stage DEA technique possible not only to appreciate the efficiency of processes and sub-processes but also determinate the weaknesses and strengths of analyzing subjects. This will aggravate the practical use of two-stage DEA technique in the evaluation of insurance companies and banks.
Application of Two-Stage DEA Technique for Efficiencies Measuring of Insurance Companies and Banks
Keywords: efficiency; evaluation; Data envelopment analysis (DEA); Two-stage DEA technique; insurance companies; banks